Using the Minor Variant Finder software to identify and quantify the allelic burden level of somatic mutations in oncohematologic diseases - T. N. Subbotina; I. E. Maslyukova; A. A. Faleeva; P. A. Nikolaeva; A. S. Khazieva; E. A. Dunaeva; K. O. Mironov; L. B. Polushkina; I. S. Martynkevich; S. V. Vereshchagina; B. V. Barankin (Онкогематология)
Background. There are problems related to both quantitative assessment of an allele burden level of a mutant gene and interpretation of results in DNA samples with the burden level of the mutant allele less than 15–20 %, when using Sanger sequencing for analyzing somatic mutations. Applied Biosystems (USA) has developed new software Minor Variant Finder, which allows determining mutations with the allele burden level from 5 %.The objective: to determine the allele burden level and identification of minor variants of somatic mutations in the ASXL1, JAK2 genes and BCR-ABL oncogene using Minor Variant Finder software in patients with myeloproliferative neoplasms.Materials and methods. The level of mutant allele burden for 15 patients with myeloproliferative neoplasms was determined by the identified mutations using the Minor Variant Finder software, after analysis of point somatic mutations in the ASXL1, JAK2 genes and BCR-ABL oncogene by Sanger sequencing.Results. The allele burden level in all 5 ASXL1-positive samples and BCR-ABL-positive sample was determined as higher than 20 % using the Minor Variant Finder software. The allele burden level in 2 cases was higher than 20 % and in 7 cases lower than 20 %, when we analyzed 9 JAK2-positive samples.Conclusion. Minor Variant Finder software can be used to estimate the allele burden level and to identify minor variants of somatic mutations in the ASXL, JAK2 and BCR-ABL genes.